Students’ Interest in Geoscience Topics, Contexts, and Methods - Hemmer, Ingrid; Bayrhuber, Horst; Häußler, Peter; Hemmer, Michael; Hlawatsch, Sylke; Hoffmann, Lore; Raffelsiefer, Marion (Zeitschrift für Geographiedidaktik (ZGD), 2007)
Geoscience topics are playing an increasingly important role with regard to the future of our planet. Consequently, they have been moving into the educational foreground because of their societal relevance. The question is, however: Are pupils interested in these topics? This is important didactically, for interest is both a prerequisite and a goal of any effective learning process. What are the topics and methods that will interest students and what are those that will not? What contexts are particularly suitable for introducing children and adolescents to geoscientific topics and methods? Do pupils show a private interest in geoscientific issues? A questionnaire was submitted to 333 German senior grammar school students aged between 17 and 19. The study generally shows a medium interest in geoscientific topics with students. The most interesting topics are those that are related to human beings or environmental threat, respectively, such as "earthquakes" or "climatic changes". The interest in a topic correlates with the context that it is related to. Young adults share a relatively high interest in the topics "individual", "society" as well as "social responsibility". Concerning special methods in class there is a particular tendency towards action-oriented working methods like the carrying out of geoscientific experiments. In their spare time youths seldom occupy with geoscientific subjects. This underlines the important role of school lessons in raising the student’s interest in these fields. In german school geography covers geoscientific contents far more than biology, while chemistry and physics insufficiently deal with them.